Potential antitumor activity of digitoxin and user-designed analog administered to human lung cancer cells - Eldawud, Reem; Wagner, Alixandra; Dong, Chenbo; Gupta, Neha; Rojanasakul, Yon; O'Doherty, George; Stueckle, Todd A.; Dinu, Cerasela Zoica (Biochimica et biophysica acta. General subjects, 2020)
Cardiac glycosides (CGs), such as digitoxin, are traditionally used for treatment of congestive heart failure; recently they also gained attention for their anticancer properties. Previous studies showed that digitoxin and a synthetic L-sugar monosaccharide analog treatment decreases cancer cell proliferation, increases apoptosis, and pro-adhesion abilities; however, no reports are available on their potential to alter lung cancer cell cytoskeleton structure and reduce migratory ability. Herein, we investigated the anticancer effects of digitoxin and its analog, digitoxigenin-α-L-rhamnoside (D6MA), to establish whether cytoskeleton reorganization and reduced motility are drug-induced cellular outcomes. We treated non-small cell lung carcinoma cells (NSCLCs) with sub-therapeutic, therapeutic, and toxic concentrations of digitoxin and D6MA respectively, followed by both single point and real-time assays to evaluate changes in cellular gene and protein expression, adhesion, elasticity, and migration. Digitoxin and D6MA induced a decrease in matrix metalloproteinases expression via altered focal adhesion signaling and a suppression of the phosphoinositide 3-kinases / protein kinase B pathway which lead to enhanced adhesion, altered elasticity, and reduced motility of NSCLCs. Global gene expression analysis identified dose-dependent changes to nuclear factor kappa-light-chain-enhancer, epithelial tumor, and microtubule dynamics signaling. Our study demonstrates that digitoxin and D6MA can target antitumor signaling pathways to alter NSCLC cytoskeleton and migratory ability to thus potentially reduce their tumorigenicity. Discovering signaling pathways that control cancer's cell phenotype and how such pathways are affected by CG treatment will potentially allow for active usage of synthetic CG analogs as therapeutic agents in advanced lung conditions. [Display omitted] •Synthetic cardiac glycoside analogs hold promise as potent anti-neoplastic agents.•Digitoxigenin-α-L-rhamnoside (D6MA) was more potent than digitoxin.•D6MA decreased lung cancer cell migration, volume, and elasticity.•D6MA suppressed PI3K/AKT and MMP expression via altered focal adhesion signaling.•D6MA potentially shifts lung cancer cell phenotype toward an epithelial-like state.